A critical review of copper electroless deposition on glass substrates for microsystems packaging applications. (3rd June 2022) - Pawar, Karan; Dixit, Pradeep
ABSTRACT: This article reviews the state-of-the-art electroless copper deposition on glass substrates and the associated challenges.The well-known issue of poor adhesion of electroless copper with the glass substrate was addressed and later, improved bymodifying the surface energy using a specific chemical treatment or by creating localized surface roughening. Localized surfaceregions in the glass were created by abrasive-based ultrasonic machining and high-temperature electrochemical-discharge machiningtechniques. The effect of critical process parameters on the surface roughness and morphology was explained. Both qualitative andquantitative adhesion measurement techniques, such as cross-hatch tests and 90°/180° peel adhesion tests, were presented. Theadhesion strength is affected by the surface roughness of the substrate and residual stress build-up in the film. As the build-up stresscan be released by the post-deposition annealing, the adhesion strength is further increased. Finally, the electroless coppertechnology in making through-glass-vias and embedded redistribution lines are presented.